Single access physician-modified fenestrated branched endovascular aortic repair for post-dissection thoracoabdominal aortic aneurysm with unilateral iliac occlusion - Kenneth Han; Herbert James, III; Alyssa Pyun; Jason Hong; Jacquelyn Paige; Sukgu Han (Annals of Vascular Surgery - Brief Reports and Innovations, 2024)
Fenestrated Branched Endovascular Aortic Repair (FBEVAR) typically requires placement of large sheaths into bilateral femoral arteries. However, for patients with hostile iliofemoral arteries due to small caliber, severe occlusive disease, or high tortuosity, various endovascular and open adjunctive techniques have been described. Here, we describe a case in which a femoral conduit was utilized to enable FBEVAR through a single access point, adding to the armamentarium of adjunctive access techniques.